Prevalence of Food Insecurity Among HIV-Positive Smokers in Vietnam - Gloria Guevara Alvarez; Reet Kapur; Trang Nguyen; Nam Nguyen; Mari Armstrong-Hough; Niyati Parekh; Donna Shelley (Tobacco Use Insights)
Introduction Smoking causes disparate health outcomes among people living with HIV, who also experience higher rates of food insecurity compared to HIV-negative adults. Objective Aiming to characterize household food insecurity among HIV + smokers in Vietnam, we surveyed 182 smokers undergoing HIV-care at 5 clinics in Hanoi, Vietnam. Methods We estimated the proportion of food insecurity among our sample using the Household Food Insecurity Access Scale and analyzed covariates associated with food insecurity, like income, and moderators of smoking, like drug use. Results Food insecurity was reported by 13.3% of our sample. The mean (SD) of years living with HIV was 12.8 (6.45). Moderate-to-severe food insecurity was associated with tobacco dependence [RR = 1.68 (1.27, 2.22); P = .05] and readiness-to-quit smoking [RR = .45 (.24, .86); P = .002]. Conclusions Our findings suggest people living with HIV who smoke are vulnerable to food insecurity and face very high or high tobacco addiction. We also find evidence that food insecurity is linked to several other conditions that alone or together are barriers to quitting. Considering these findings and the increasing interest in HIV and co-existing chronic conditions like smoking and food insecurity, further research is needed to understand how food insecurity and tobacco use intersect and impact people living with HIV who experience these concomitant conditions.